Managing the quality of the design and implementation of common task assessment in Sedibeng–East and Sedibeng–West schools - Malapo, Anna Lebohang (North-West University, 2013)
This study examines the design and implementation of Common Task Assessment as a Grade 9 summative assessment specifically of Economic Management Sciences. The main focus is on understanding how the quality of the design and implementation thereof at Sedibeng-West and Sedibeng-East schools are managed. The research was undertaken in response to the researcher's personal observation and experience of how educators were struggling to implement Common Task Assessment, due to lack of resources and the challenges they faced in implementing new policies introduced by the Department of Education. From an international perspective, the literature reveals that Common Task Assessment is problematic in other countries as well, so it is not abnormal to discover similar problems emerging at South African schools during implementation. This thesis presents an overview of the relevant literature which was studied in order to validate the research problem: gaining a perspective on how the design and the implementation of Common Task Assessment concerning the Economic Management Sciences are presently managed at Sedibeng-East and Sedibeng-West schools. Attention was focused on aspects such as the conceptual framework on which the study was grounded, namely that there is a very specific societal relationship within a school which should be honoured at all times. The research paradigm was based on a positivist and post positivist worldview and the empirical investigation comprised of quantitative research, combined with a small dimension of qualitative research. The strategy of inquiry was non-experimental, descriptive survey research carried out with the participation of on Grade 11 learners who had completed the Common Task Assessment of Economic Management Sciences in 2009 and Grade 9 educators who teach this subject. Two structured questionnaires (one for learners and the other for educators) were used, consisting of Likert scale and open-ended questions. Key issues were identified, bolstering strengths and combatting weaknesses in managing the design and implementation of school-based assessment. Educators and learners‟ data revealed far-reaching implications for Common Task Assessment, which should be taken into consideration in order to improve this type of assessment instrument. In everything ethical principles were strictly adhered to. The results from the data analyses were organized into themes concerning the design of Common Task Assessment, as well as the implementation and management thereof. Challenges put forward by learner participants, as well as those put forward by educators, received prominence and the urgency of training educators in the implementation of school-based assessment was accentuated. Findings made from the literature study were compared with those which emerged from the questionnaires, simplifying the task of highlighting the contributions of the study to the theory and the practice of managing school-based assessment and the logic of the recommendations. The thesis suggests numerous guidelines toward a management intervention plan to improve the quality of the design and implementation of school-based assessment. These guidelines were compiled in line with the aims and principles of the New Curriculum Statement (CAPS). The main thrust of the research is therefore not the negative aspects which were identified, but the positive assurance that managing school-based assessment professionally while keeping it CAPS relevant, is not an insurmountable task.
"PhD awarded posthumously."--p.22, Autumn Graduation Ceremony, North-West University, Vaal Triangle Campus, 2013
Keywords: Managing; Quality; Implementation; Common task; Assessment; Sedibeng-East; Sedibeng-West; Schools